2019
DOI: 10.1002/alr.22298
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and imaging findings of respiratory epithelial adenomatoid hamartoma: a systematic review

Abstract: BackgroundRespiratory epithelial adenomatoid hamartoma (REAH) is a recently classified histopathologic diagnosis often identified incidentally following endoscopic sinus surgery (ESS) for presumed chronic rhinosinusitis. Limited data exist defining preoperative imaging features and surgical outcomes. The purpose of this study is to examine characteristic imaging findings of REAH and postoperative olfactory and recurrence outcomes.MethodsA systematic review was performed according to the Preferred Reporting Ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 17 publications
4
33
0
2
Order By: Relevance
“…REAH frequently occurs in the central compartment of the nasal cavity, with the posterior nasal septum and OC being the most commonly reported locations. 9,13 Although location reported varies by study and sampling method, many authors have identified an association with middle turbinate lateralization picked up as an enlarged, opacified OC on computed tomography (CT) imaging. Seven out of 10 studies assessed for imaging findings in a recent systematic review found evidence of OC enlargement/involvement, with one study reporting that OC width greater than 10 mm resulted in 88% sensitivity for REAH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…REAH frequently occurs in the central compartment of the nasal cavity, with the posterior nasal septum and OC being the most commonly reported locations. 9,13 Although location reported varies by study and sampling method, many authors have identified an association with middle turbinate lateralization picked up as an enlarged, opacified OC on computed tomography (CT) imaging. Seven out of 10 studies assessed for imaging findings in a recent systematic review found evidence of OC enlargement/involvement, with one study reporting that OC width greater than 10 mm resulted in 88% sensitivity for REAH.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is further supported by the finding that the main treatment for CCAD-conservative resection and sculpting of abnormal appearing mucosa down to as normal appearing anatomy as possible without exposing underlying bone-has resulted in low rates of recurrence for both REAH and CCAD. [5][6][7]9,13,19 Further studies will be necessary to investigate the pathogenesis of REAH and related disease in the central compartment of the nasal cavity. This study was limited by its retrospective nature, as the true rate of allergy could not be fully assessed in some patients due to lack of documentation of allergy status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations